Assessment of Scalable Fractionation Methodologies to Produce Concentrated Lauric Acid from Black Soldier Fly (Hermetia illucens) Larvae Fat - Luis Vázquez; Carlota Reyero; Raúl Hurtado-Ribeira; David Villanueva-Bermejo; Alejandro Belinchón; José Palomar; Tiziana Fornari; Diana Martín (Insects)
In the present study, different methodologies with potential scalability and environmental friendliness, such as winterization, supercritical fluid extraction, and multistage distillation, were evaluated for lauric acid concentration. In all cases, to facilitate fractionation, the transformation of triacylglycerols into free fatty acids or fatty acid ethyl esters was required as a previous step. For the winterization experimental assays, the amount and type of solvent was studied, resulting in a product containing ~65% lauric acid with a recovery of ~81% using a 1:10 oil-to-solvent ratio with hexane. On the other hand, the experimental extraction with supercritical carbon dioxide in a counter current packed column at 55 °C, 115 bar, and 70 g CO2/min, resulted in a product composed of ~80% lauric acid as ethyl ester with a recovery of ~85%. Finally, flash and multistage distillation were analysed using process simulation (Aspen Plus V14), demonstrating that this methodology can achieve 80% recovery with high purity (lauric acid: 96.7%; ethyl laurate: 97.4%), but a high vacuum is required to prevent thermal degradation of the product (lauric acid: 0.2 mbar; ethyl laurate: 1.1 mbar). Overall, the employed methodologies proved highly efficient in concentrating lauric acid, yielding a product of commercial interest and high added value.